Pengaruh Komitmen Organisasi, Disiplin Kerja, dan Semangat Kerja Terhadap Kinerja Karyawan Bank Kalsel Cabang Utama Banjarmasin - Marisa Hardiyanti Shallim Putri; Titien Agustina; TA Hariyono; Muhammad Jahri (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2021)
Bank Kalsel Cabang Utama Banjarmasin always improve customers services. The improvement need the high performance of employee. The Performance is influenced by organizational commitment, work discipline, and employee morale. To analyzing the influence commitment, work discipline, and employee morale to the performance need the research. This research uses quantitative method. The population is all members of this research 74 employee. The population are consist of 74 respondens. Technique of sampling is used census. This research sample 74 employee. The data collection technique is questioner. Data is analyzed by linier regression analysis The results of this research shows that commitment, work discipline, and employee morale have influence significantly to the performance partially and together. So commitment, work discipline, and employee morale are need to improve because these variables have influence significantly to the performance.